Identifying the metabolic 'Achilles heel' of adult and paediatric glioblastoma multiforme - Wood, James (2019)
Despite substantive efforts to characterise glioblastoma multiforme (GBM) at the molecular level, improvements to the overall survival of patients have yet to be seen within the clinic. Intratumour heterogeneity describes the co-existence of several subpopulations of GBM cells that are genetically distinct. This phenomenon provides one mechanism by which GBM recurs via the presence of resistant subclonal cells. However, questions remain as to whether cancer cell metabolism demonstrates the same level of heterogeneity given the metabolic regulatory role of several oncogenes and tumour suppressors. We applied liquid chromatography-mass spectrometry to profile the metabolome and lipidome of tumour fragments sampled from adult GBM patients. The extent of heterogeneity in metabolomic and lipidomics profiles differed between patients but was predominantly observed between non-invasive and invasive regions. Evidence for normal brain metabolism influencing the metabolomic profile of the invasive region was detected, calling for isolation of the tumour cell component. Despite this caveat, dysregulated proline metabolism was identified for further mechanistic and therapeutic study.